Predictive Factors of Growth Among Preterm Migrant Children in Kanchanaburi Province, Thailand - Noijeen, Nidkamoln; Rungamornrat, Somsiri; Srichantaranit, Arunrat (Journal of Population and Social Studies [JPSS], 2021)
This research sought to study the predictive factors of the duration of exclusive breastfeeding, mother’s feeding behaviors, and health service accessibility on the growth of preterm migrant children in Kanchanaburi Province, Thailand. The subjects were 156 Burmese migrant mothers with preterm children 18-24 months old who received health check-ups at well-baby clinics in Kanchanaburi Province. The data analysis was performed utilizing descriptive and multiple logistic regression statistics. The results revealed that although premature infants should reach normal growth the same as full-term children at 2 years old, 41% of the child subjects were underweight, and 46.8% had stunted growth. Also, 53.2% of the mothers exclusively breastfed for less than 6 months due to the mothers having to return to work. Upon performing multiple logistic regression analysis, it was found that exclusive breastfeeding from birth to the age of 6 months old and the feeding behaviors of the mothers were the most significant predictors influencing the growth of premature migrant children. In comparison, health service accessibility did not affect the growth of premature migrant children since the majority of migrant mothers (88.5%) regularly brought their preterm children for health check-ups. Our findings strongly suggested that the education of migrant mothers should be continuously promoted to emphasize the importance of exclusive breastfeeding of their preterm children, including in their workplace, and to encourage migrant mothers to recognize the importance of providing complementary foods to suit their migrant Burmese lifestyle.